Long-Term Clinical Effectiveness of a Drug-Coated Balloon for the Treatment of Femoropopliteal Lesions: Five-Year Outcomes From the IN.PACT SFA Randomized Trial - Laird, John A. (Circ Cardiovasc Interv, 2019)
BACKGROUND: While randomized trials have demonstrated the superiority of drug-coated balloon (DCB) angioplasty versus standard percutaneous transluminal angioplasty (PTA) in patients with femoropopliteal peripheral artery disease, the long-term durability of DCB angioplasty remains uncertain. METHODS AND RESULTS: IN.PACT SFA is a prospective, multicenter, randomized single-blinded trial (Randomized Trial of IN.PACT Admiral Paclitaxel-Coated Percutaneous Transluminal Angioplasty [PTA] Balloon Catheter vs Standard PTA for the Treatment of Atherosclerotic Lesions in the Superficial Femoral Artery [SFA] and/or Proximal Popliteal Artery [PPA]) that enrolled 331 subjects with symptomatic (Rutherford 2–4) femoropopliteal lesions. Subjects were randomly assigned 2:1 to the IN.PACT Admiral DCB or PTA. Assessments through 5 years included freedom from clinically driven target lesion revascularization, the primary safety end point, and major adverse events. Through 5 years, patients treated with the IN.PACT Admiral DCB demonstrated a sustained treatment effect with superior freedom from clinically driven target lesion revascularization when compared with PTA (Kaplan-Meier estimate of 74.5% versus 65.3%; log-rank P=0.020). The primary safety composite was achieved in 70.7% of subjects in the DCB and 59.6% in the PTA groups (P=0.068). The major adverse event rate was 42.9% for DCB and 48.1% for PTA (P=0.459). There were no device- or procedure-related deaths in either group as adjudicated by an independent and blinded Clinical Events Committee. CONCLUSIONS: The IN.PACT SFA randomized trial demonstrates that the IN.PACT Admiral DCB continues to perform better than PTA through 5 years with higher freedom from clinically driven target lesion revascularization. The sustained safety and effectiveness profile of this DCB supports its use as a preferred treatment choice compared with PTA for femoropopliteal lesions. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01175850 (IN.PACT SFA phase I) and NCT01566461 (IN.PACT SFA phase II).